Multi-Criteria Decision Making for Photovoltaic Alternatives: A Case Study in Hot Climate Country - Miraj, Perdana; Berawi, Mohammed Ali (International Journal of Sustainable Energy Planning and Management, 2021)
Photovoltaic (PV) experiences significant growth and has installed in many locations worldwide over the past decades. However, selecting the best alternative of PV system remains a problem in developing countries which often involves both interest and multiple objectives and from stakeholders. This research aims to select ideal PV model in an isolated island in the eastern part of Indonesia. Multi-criteria decision making (MCDM) will provide an ideal solution that uses a systematic process of decision making. This research proposes an alternative concept of MCDM by taking into account best-worst method and VIKOR method. In general, the main purpose of the both methods are to obtain weights and rank alternatives with the advantages of less information required and produce a more consistent result compared to AHP method. The result shows the best alternative for PV installation, which offers the highest power and potentially developed not only for daily access to electricity but also to support economic activities such as tourism and aquaculture.